2015
DOI: 10.1063/1.4916707
|View full text |Cite
|
Sign up to set email alerts
|

The origin of ferroelectricity in Hf1−xZrxO2: A computational investigation and a surface energy model

Abstract: The structural, thermal, and dielectric properties of the ferroelectric phase of HfO2, ZrO2 and Hf0.5Zr0.5O2 (HZO) are investigated with carefully validated density functional computations.We find, that the free bulk energy of the ferroelectric orthorhombic Pca21 phase is unfavorable compared to the monoclinic P21/c and the orthorhombic Pbca phase for all investigated stoichiometries in the HfχZr1-χO2 system. To explain the existence of the ferroelectric phase in nanoscale thin films we explore the Gibbs / Hel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

44
684
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 663 publications
(765 citation statements)
references
References 68 publications
44
684
0
2
Order By: Relevance
“…By comparing the Helmholtz free energies of various HfO 2 (and Hf 0:5 Zr 0:5 O 2 ) phases, it was found that the o-phase became the lowest-in-energy for HfO 2 when the grain size was 3-5 nm (8-16 nm for Hf 0:5 Zr 0:5 O 2 Þ. 37 On the other hand, experimentally, Yurchuk et al 36 first reported that in Si: HfO 2 thin films, as the film thickness increased from 9 nm to 27 nm, the P r dropped from 24 C/cm 2 to 3.5 C/cm 2 . The similar inverse relation between P r and film thickness was also found in undoped HfO 2 38 and Hf 0:5 Zr 0:5 O 2 solid solution films.…”
Section: Origins Of Ferroelectricity In Hfo 2 -Based Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…By comparing the Helmholtz free energies of various HfO 2 (and Hf 0:5 Zr 0:5 O 2 ) phases, it was found that the o-phase became the lowest-in-energy for HfO 2 when the grain size was 3-5 nm (8-16 nm for Hf 0:5 Zr 0:5 O 2 Þ. 37 On the other hand, experimentally, Yurchuk et al 36 first reported that in Si: HfO 2 thin films, as the film thickness increased from 9 nm to 27 nm, the P r dropped from 24 C/cm 2 to 3.5 C/cm 2 . The similar inverse relation between P r and film thickness was also found in undoped HfO 2 38 and Hf 0:5 Zr 0:5 O 2 solid solution films.…”
Section: Origins Of Ferroelectricity In Hfo 2 -Based Materialsmentioning
confidence: 99%
“…37 In their work, Materlik et al 37 built the Helmholtz free energy model, which contain both an ab initio computed part for total energy and entropy, and a phenomenological part for the surface energy. By comparing the Helmholtz free energies of various HfO 2 (and Hf 0:5 Zr 0:5 O 2 ) phases, it was found that the o-phase became the lowest-in-energy for HfO 2 when the grain size was 3-5 nm (8-16 nm for Hf 0:5 Zr 0:5 O 2 Þ.…”
Section: Origins Of Ferroelectricity In Hfo 2 -Based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The free energy change that may lead to formation of a metastable structure can be due to a combination of finite-temperature (primarily vibrational entropy) effects, finite-size (surface) effects, strain, and "doping" (alloying). These aspects have recently been discussed from a theoretical perspective [19][20][21][22]45]; in particular, changes in the relative free energy of several HfO 2 , ZrO 2 , and HfZrO 4 phases have been estimated by Materlik et al [19], who reported that within a wide range of experimentally reasonable conditions and for film thicknesses in 9nm…30 nm range the vibrational entropy, surface, and strain contributions are well within <∼180 meV/f.u. The changes due to intentional "doping" (alloying) need be evaluated on a case-by-case basis but can be expected to be <<∼ 50 meV/f.u.…”
mentioning
confidence: 99%
“…This discovery is of great interest to the semiconductor industry and has led to intensive experimental [3][4][5][6][7][8][9][10][11][12][13][14] and theoretical [9,[15][16][17][18][19][20][21][22] research, because these materials are believed to avoid the problems typical for the traditional ferroelectric materials (such as lead zirconate titanate) during integration into microelectronic devices. However, precise identification of the phase(s) in these films is problematic due to experimental limitations such as the broadness of the thin-film diffraction spectra, unknown film texture and strain fields, and possible presence of multiple phases within a single film.…”
mentioning
confidence: 99%